Optimization of Flow Characteristics and Diffusion Angles of Forward Inflow Forebay of Pumping Station - LI Yun; LI Chaochao; LI Mingyang; GU Jingchao (Renmin Zhujiang)
To address issues arising from chaotic water flow due to unreasonable pumping station operation and insufficient forebay design, this study took the Yanhuangding pumping station as a typical case. Numerical simulations using FLUENT software were conducted to examine different forebay patterns based on the Realizable turbulence model and the Eulerian multiphase flow model. The influences of different diffusion angles and different number of operating pumping stations on the flow field structure in the forebay were expounded. The results show that: ① As the diffusion angle increases, the number of vortices in the forebay flow rises from one to two. At diffusion angles of 25°and 30°, the vortex area occupies less of the forebay inflow, resulting in a more stable flow field. ② Reducing the number of operating pumping stations from five to two decreases the vortex area in the forebay from 31.42 m2 to 10.15 m2, with optimal forebay flow achieved when operating pumping stations 3# and 4#. The research results can provide reference and guidance for the design and renovation of similar pumping stations.